Influences of climate and nutrient enrichment on the multiple trophic levels of Turkish shallow lakes. Issue 2 (2nd April 2020) - Beklioğlu, Meryem; Bucak, Tuba; Levi, Eti E.; Erdoğan, Şeyda; Özen, Arda; Filiz, Nur; Bezirci, Gizem; Çakıroğlu, Ayşe İdil and Tavşanoğlu, Ü. Nihan and Gökçe, Didem and Demir, Nilsun and Özuluğ, Müfit and Duran, Mustafa and Özkan, Korhan and Brucet, Sandra and Jeppesen, Erik
ABSTRACT: Climate warming threatens the structure and function of shallow lakes, not least those in the Mediterranean climate. We used a space-for-time substitution approach to assess the response of trophic and community structures as well as the richness and evenness of multiple trophic levels to temperature, hydrological, and nutrient constraints. We selected 41 lakes covering wide climatic, hydrological, and nutrient gradients within a short distance for reducing the effect of biogeographical factors in the western Anatolian plateau of Turkey. Generalized linear model analyses revealed that temperature was overall the most important driving variable, followed by total nitrogen (TN) and salinity. The chlorophyll a :total phosphorus ratio, the cyanobacteria:total phytoplankton biovolume ratio, the fish:zooplankton biomass ratio, the proportion of small fish, and fish richness increased with increasing temperature, whereas macrophyte plant volume inhabited (PVI, %), richness, and evenness decreased. Grazing pressure, macrophyte coverage, piscivore biomass, phytoplankton richness, and evenness decreased significantly with both increasing TN and temperature. Temperature and nutrients also separated the northern highland lakes from other lakes in a non-metric multidimensional scaling analysis. Additionally, salinity reduced richness and evenness of phytoplankton and zooplankton. Our results indicate major changes in lake structure and functioning with warming and eutrophication, and highlight the need for strict control of nutrients and water use.